Investigation on the impact wear behavior of 2.25Cr–1Mo steel at elevated temperature - Chen, Xu-dong; Wang, Li-wen; Yang, Ling-yun; Tang, Rui; Yu, Yan-qing; Cai, Zhen-bing (Wear, 2021)
The impact wear test of 2.25Cr–1Mo steel against Gr5C12 alloy was performed at a controlled kinetic energy impact wear rig. The effect of temperatures (from 25 °C to 450 °C) on the impact wear damage mechanism was investigated. The contact force, energy absorption, and interface deformation during the impact process were recorded and analyzed in real time. Wear volume, morphology, and elemental distribution of the wear scars were used to characterize wear and tribo-chemistry behavior. Results demonstrate that at varied temperatures, the interface behavior of 2.25Cr–1Mo steel is different. With the rise in temperature, both the contact force, absorption energy, and wear volume first increase and then decrease. The explanation is that higher temperatures can modify the material's surface properties. Delamination, plastic deformation, and oxidative wear are the major mechanisms of impact wear, but the proportions of the three wear mechanisms differ at varied temperature. •The impact wear behavior of 2.25Cr–1Mo steel at elevated temperature was investigated.•The interface behavior of impact wear was analyzed.•The impact wear mechanism of 2.25Cr–1Mo steel at elevated temperature was discussed.